Analysis of the failure state of the Cenozoic clay layer in thin bedrock coal seam mining: A case study of Sanyuan coal mine - Guangming Wu; Mingbin Wang; Lei Wang (PLoS ONE, 2026)
A mechanical analysis model was constructed for the clay layer. Using a combined approach of theoretical analysis and numerical simulation, the failure state of this layer during coal seam extraction under thin bedrock conditions was investigated. The findings offer insights for evaluating the water-blocking performance of the Cenozoic clay layer and for preventing water inrush disasters in similar geological settings. The key findings are as follows: (1) The most critical factor governing clay layer failure is the amount of bedrock subsidence following collapse. As the subsidence of the fractured bedrock increases, the suspended section of the overlying clay layer extends, elevating its possibility to shear or tensile failure. (2) Variations in bedrock thickness markedly influence the subsidence of both the bedrock and the clay layer. Consequently, bedrock thickness is a primary determinant of the degree of damage sustained by the clay layer. (3) The minimum bedrock thickness required to prevent failure of the basal clay layer within the Cenozoic overburden ranges from 33 m to 38 m. If the bedrock thickness falls below 33 m, the clay layers will be damaged after coal seam mining, leading to a loss of their water-blocking capacity.